Prospect of Bioremediation Using Synthetic Biology Approach in Indonesia - Kemal, Rahmat Azhari; Novianti, Annisa; Rini, Ika A.; Fatmawati, Ruli (Proceeding International Conference on Global Resource Conservation, 2015)
Cellular systems can be engineered by synthetic biology approach to make a controllable bioremediation system. Several teams competing in the International Genetically Engineered Machine (iGEM) competition have utilized the potency of synthetic biology for bioremediation. This review highlighted several ideas. One of them is the designing a whole-cell biocatalyst that can degrade PET component in plastic waste. Rice blast (Magnaporthe grisea) produces cutinase, thus its gene encoding cutinase can be used as substitute in the system. Regulation of the application is also discussed. It is hoped that research and implementation of bioremediation using synthetic biology in Indonesia can be developed.Keywords: Biodiversity; bioremediation; iGEM; Indonesia; synthetic biology